Pembangunan Sistem Pengelolaan Pengajuan Kegiatan Mahasiswa Universitas Brawijaya - Dainty Resfulany Susanto; Denny Sagita Rusdianto; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The manual of procedures of student event submission in Brawijaya University (UB) has a disadvantage. The disadvantage is Student Sovereignty Institutions (LKM) need to follow up their submission for each procedure because there is no information about submission status. Currently, the follow-up processes often get some problems such as the absence of UB's student affairs staff and/or their submission status has not been changed so that the follow-up processes need to be repeated. Meanwhile, UB's student affairs also need a management system to manage student event submission because in every month there are so many proposals. These problems can be solved by a system that can help the arrangement and management of submission processes. The system was created in the web-based, so users can use this system anywhere and anytime. This system has been tested through the white-box method for the unit and the integration testing of 3 sample methods from several classes get 100% valid result. Then, 23 functional requirements have been tested by black-box testing for validation testing get 100% valid result.